Importance of the Flora promising medicinal of Jesus, Cajamarca, Peru - Mostacero-León, José (2020)
It is indisputable, the role that flora and particularly medicinal plants play in improving the quality of life of the world population. In Peru, knowledge about plants and their applications has been transmitted throughout history and today constitutes a legacy inherited by the Andean-Amazon communities, which are possessors of an exceptional, unique and promising flora; and unfortu- nately these traditions are gradually being lost, especially due to demographic expansion. Based on what has been described, this research aims to determine the importance of the promising medicinal flora of Jesus, Cajamarca, Peru. For this, 96 semi-structured interviews were applied, using the “snowball” technique, in order to collect data regarding taxonomic characters: family, scientific and common name, as well as ethnomedical characters: part used, type of preparation, method of administration, treated disease or illness, and Use Value index, of each species. It is reported for the Jesus district, 24 species of Flora promising medical, distributed in 23 genera and 18 families; being, the most representative for their number of species, the Asteraceae (3), Lamiaceae (3) and Fabaceas (2). Finally, of this total, 18 promising species were considered important by the inhabitants of the Jesús district, according to their Use Value Index (IVU).